Divergent patterns of meiotic double strand breaks and synapsis initiation dynamics suggest an evolutionary shift in the meiosis program between American and Australian marsupials - Valero-Regalón, F. Javier; Solé, Mireia; López-Jiménez, Pablo; Valerio-de Arana, María; Martín-Ruiz, Marta; de la Fuente, Roberto; Marín-Gual, Laia; Renfree, Marilyn B.; Shaw, Geoff; Berríos, Soledad; Fernández-Donoso, Raúl; Waters, Paul D.; et al. (Frontiers in Cell and Developmental Biology, 2023)
In eutherian mammals, hundreds of programmed DNA double-strand breaks (DSBs) are generated at the onset of meiosis. The DNA damage response is then triggered. Although the dynamics of this response is well studied in eutherian mammals, recent findings have revealed different patterns of DNA damage signaling and repair in marsupial mammals. To better characterize these differences, here we analyzed synapsis and the chromosomal distribution of meiotic DSBs markers in three different marsupial species (Thylamys elegans, Dromiciops gliorides, and Macropus eugenii) that represent South American and Australian Orders. Our results revealed inter-specific differences in the chromosomal distribution of DNA damage and repair proteins, which were associated with differing synapsis patterns. In the American species T. elegans and D. gliroides, chromosomal ends were conspicuously polarized in a bouquet configuration and synapsis progressed exclusively from the telomeres towards interstitial regions. This was accompanied by sparse H2AX phosphorylation, mainly accumulating at chromosomal ends. Accordingly, RAD51 and RPA were mainly localized at chromosomal ends throughout prophase I in both American marsupials, likely resulting in reduced recombination rates at interstitial positions. In sharp contrast, synapsis initiated at both interstitial and distal chromosomal regions in the Australian representative M. eugenii, the bouquet polarization was incomplete and ephemeral, γH2AX had a broad nuclear distribution, and RAD51 and RPA foci displayed an even chromosomal distribution. Given the basal evolutionary position of T. elegans, it is likely that the meiotic features reported in this species represent an ancestral pattern in marsupials and that a shift in the meiotic program occurred after the split of D. gliroides and the Australian marsupial clade. Our results open intriguing questions about the regulation and homeostasis of meiotic DSBs in marsupials. The low recombination rates observed at the interstitial chromosomal regions in American marsupials can result in the formation of large linkage groups, thus having an impact in the evolution of their genomes.